KARAKTERISTIK OLAH GERAK KAPAL DALAM PENGGUNAAN DUAL FOIL NACA 0012 PADA MONOHULL DAN PENTAMARAN DENGAN MENGGUNAKAN SIMULASI CFD - Muhammad Iqbal (2023)
When a ship is in motion, it experiences six degrees of freedom or oscillatory motion. These movements are surge, sway, heave, roll, pitch, and yaw. The Response Amplitude Operator (RAO) is defined as the ratio of the ship's motion amplitudes (translation and rotation) to the wave amplitude at a specific frequency. A higher RAO value indicates larger motions felt by the ship. This study focuses on monohull and pentamaran vessels with a displacement condition of 0.011 m^3, using the parameter conditions of Lx (2c, 2c, 2c) and Ly (1c, 0.7c, 0.5c). The research is supported by Maxsurf Modeler and Rhinoceros 6.0 software for modeling the monohull and pentamaran vessels, respectively. Ansys AQWA is used to obtain the RAO values. From the simulations conducted, Through the simulations conducted, it was found that the hull form affects the RAO values. The Pentamaran model shows smaller RAO values compared to the monohull model. This can be observed in the reduction of the average percentage of RAO values for heave by 0.54% and pitch by 0.9% compared to the monohull model.